POST HARVEST SOIL FERTILITY AND BIOLOGICAL STATUS EFFECTS ON SORGHUM PRODUCTIVITY AS INFLUENCED BY PRECEDING LEGUMES, NITROGEN LEVELS AND IRRIGATION SCHEDULES - RVT.BALAZZII NAAIIK, A. MADHAVI, J.S.MISHRA, R.G.PRABHAKARA, R.SUBHASH REDDY; V.RAJA RAJESWARI (The Journal of Research ANGRAU, 2015)
The present investigation (2012-2014) explored the possibility of exploiting the beneficial effects of growing dhaincha and its in situ incorporation at flowering in kharif as a preceding crop to improve the soil physical, chemical and biological status. The experiment was carried out in strip – split plot design with three replications. Four strips of treatments including dhaincha, greengram and cowpea raised as preceding kharif legumes along with fallow are taken as main plot treatments. During rabi, sorghum was grown in split plot design taking strips of kharif crops as main plots, four irrigation schedules assigned to sub – plots and four nitrogen levels viz., 0, 30, 60 and 90 kg ha-1 to sub - sub plots. Initially the soil was slightly alkaline by in situ incorporation at flowering in kharif as a preceding crop followed by irrigation (at the critical stages) at panicle initiation, boot leaf, anthesis and milking stage of the grains and application of nitrogen 60 kg ha-1 reduced the pH and EC. The microbial population viz., bacteria, fungi and actinomycetes were found in large number in the rhizosphere of sorghum in response to the preceding kharif legumes. Higher bacteria (74 × 106 CFUg-1 of soil), fungi (15 × 104 CFUg-1 of soil) and actinomycetes (33 × 103 CFUg-1 of soil) were found with green manuring i.e. dhaincha in situ incorporation in preceding kharif season. Highest microbial population was observed with irrigation at four critical stages. The microbial population in rhizosphere of sorghum increased significantly (bacteria: 22-60 × 106), (fungi - 05 - 14 × 104) and (actinomycetes: 13-28 × 103) with application of nitrogen 30 to 60 kg N ha-1 and thereafter the increase was insignificant. Higher grain yield of sorghum was obtained by growing dhaincha for green manure or greengram for seed with four irrigations at critical phases of panicle initiation, booting, anthesis and milk stage along with application of 60 kg N ha-1.